Intake of foods high in saturated fats, vegetarian dietary pattern, and sociodemographic characteristics associated with body weight in Peruvian university students - Saintila, Jacksaint; Ruiz Mamani, Percy G.; Ramos-Vera, Cristian; Serpa-Barrientos, Antonio; Oblitas-Guerrero, Susan M.; Lizarraga-De-Maguiña, Isabel G.; Calizaya-Milla, Yaquelin E. (Frontiers in Nutrition, 2024)
The prevalence of obesity continues to increase among university students and the general population. Consumption of a diet high in saturated fats could be one of the risk factors. Objective: The consumption of foods high in saturated fats, the vegetarian diet pattern, and sociodemographic characteristics associated with excess body weight (overweight/obesity) were evaluated in Peruvian university students.A cross-sectional study was carried out selecting 5,608 Peruvian university students through no probabilistic convenience sampling. The survey was carried out during the months of February and April 2022. The Chi-square test and binary logistic regression analysis were used to evaluate the association between diet (saturated fats intake and dietary pattern) and sociodemographic factors with excess body weight in a cross-sectional analysis. Results: It was observed that students who reported high consumption of foods high in saturated fats (ORB = 1.14) and those who had a nonvegetarian dietary pattern (ORB = 2.76) were found to be more likely to have excess body weight. On the contrary, students who reported adherence to the vegetarian diet pattern for more than 5 years were less likely to be overweight or obese (ORB = 0.84).Being ≥ 26 years of age (ORB = 3.28), living in urban areas (ORB = 1.68) and coastal areas of the country (ORB =1.17), and enrolled in the engineering faculty (ORB =1.19), were significantly associated with excess body weight. Conclusions: The findings of the current study evidenced several factors associated with excess body weight in university students. Therefore, it is necessary to promote and implement healthy lifestyle programs, considering sociodemographic and dietary aspects such as age and dietary intake to control and prevent obesity in university students.